2008
DOI: 10.1109/tmi.2008.929106
|View full text |Cite
|
Sign up to set email alerts
|

Methods of Artificial Enlargement of the Training Set for Statistical Shape Models

Abstract: Due to the small size of training sets, statistical shape models often over-constrain the deformation in medical image segmentation. Hence, artificial enlargement of the training set has been proposed as a solution for the problem to increase the flexibility of the models. In this paper, different methods were evaluated to artificially enlarge a training set. Furthermore, the objectives were to study the effects of the size of the training set, to estimate the optimal number of deformation modes, to study the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 24 publications
0
30
0
Order By: Relevance
“…Statistical models (SM) have become widely used in the field of computer vision and medical image segmentation over the past decade [26,[45][46][47][48][49][50][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88]. Basically, SMs use a priori shape information to learn the variation from a suitably annotated training set, and constrain the search space to only plausible instances defined by the trained model.…”
Section: Statistical Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Statistical models (SM) have become widely used in the field of computer vision and medical image segmentation over the past decade [26,[45][46][47][48][49][50][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88]. Basically, SMs use a priori shape information to learn the variation from a suitably annotated training set, and constrain the search space to only plausible instances defined by the trained model.…”
Section: Statistical Modelsmentioning
confidence: 99%
“…Other techniques focus on artificially enlarging the size of the training set. Koikkalainen et al [85] concluded that the two best enlargement techniques were the non-rigid movement technique and the technique that combines PCA and a finite element model.…”
Section: Active Shape Modelmentioning
confidence: 99%
“…This problem becomes more critical in medical image analysis due to inadequate training samples and varied pathologies. There have been strategies to relieve the over constraint, including loosening up the shape constraints [2,3], introducing additional flexibility [4], synthesising additional training samples [5], and more recently, modifying shape prior using manifold learning [6] or sparse composition [7]. In these methods there is no obvious a priori optimal parameters and it is time consuming to tune the parameters to specific applications.…”
Section: Introductionmentioning
confidence: 99%
“…To explicitly add shape variability to the models, a second popular approach consists of combining the statistical models with synthetic modes of variations (Lötjönen et al, 2005;Tölli et al, 2006;Koikkalainen et al, 2008). The types of deformation can be chosen to reflect expected variations, either through finite element analysis (Cootes et al, 1995;Wang and Staib, 2000) or heuristically (de Bruijne et al, 2003;Sclaroff and Isidoro, 2003).…”
Section: Introductionmentioning
confidence: 99%